Використання локальних економіко-математичних моделей в агроекології - Чистякова, В. Ф.; Chystiakova, V.; Герасимова, І. Г.; Gerasimova, I. (Дніпровський державний аграрно-економічний університет, 2015)
Стверджується, що одним з основних шляхів подолання екологічної кризи в нашій країні має стати інтеграція інтересів екології і економіки в усіх секторах аграрного виробництва, а також в аграрній освіті. Процес безперервної екологічної освіти стає надзвичайно важливим. Еколого-освітня складова має бути присутньою в усіх навчальних програмах. Єднальною дисципліною може виступити системологія. Математичне моделювання, один з інструментів системного аналізу, дозволить у ряді випадків уникнути трудомістких і дорогих натурних експериментів. Пропонується розробка комп’ютерної технології планування землеробства на зрошуваних землях у середовищі електронної таблиці Excel. One of basic ways of overcoming of ecological crisis in our country, there is integration of a few parts, namely, interests of ecology and economy in all spheres of agrarian production, and also in agrarian education. Especially important is a process of continuous ecological education. Ecological component must be in all educational disciplines. As connective discipline can be systemology. A mathematical modeling is one of system analysis instrument, that allows in most of cases to avoid intensive labour and expensive model experiments.The substantial factor of achievement balanced agrarian system is the optimal use of the landed resources. To attain the terms of balance of natural and managed by a man ecosystems, it is possible by correlation extensively and intensively using areas and natural environment complexes. It is possible to name creation of local models of optimal landfarming the instruments of this direction with the purpose of providing ecologically safed, economically balanced cooperation of agrarian production and environment. Development of computer technology of planning in agriculture is offered on irrigable land in Excel.
The use of local economy-mathematical models is in agroecology
Keywords: агроекологія; agroecology; екологічний професіоналізм аграрія; ecological professionalism; екологізація освіти; ecologization of education; системний підхід; approach of the systems; системний аналіз; system analysis; математичне моделювання; mathematical modeling; локальні моделі оптимального землекористування; local models of optimal landfarming